2019
DOI: 10.1002/smll.201904695
|View full text |Cite
|
Sign up to set email alerts
|

3D‐Printed Scanning‐Probe Microscopes with Integrated Optical Actuation and Read‐Out

Abstract: realized as a sharp tip with nanometersize apex attached to a micrometer-scale cantilever. In current SPM systems, tip and cantilever are usually structured in a dedicated microfabrication process before being manually mounted and aligned to a macroscopic optomechanical system for piezoelectric actuation and optical detection of sub-nanometer movements. This concept leads to rather bulky implementations and requires laborious operation, given that the tip is a wear part that has to be regularly exchanged and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 45 publications
0
27
0
Order By: Relevance
“…This hybrid photonic integration coupling induced by TPP paves the way for automated assembly of photonic multi-chip systems with unprecedented performance and versatility. For multi-fiber integrated microoptics, this group also demonstrated a highly compact scanningprobe microscopes (SPM) with integrated optical actuation and read-out (Dietrich et al, 2020), as shown in Figure 3F. The SPM engine was composed of cantilevers and probe tips, and integrates optical actuation and read-out by combining mirrors and lenses.…”
Section: Micro-opticsmentioning
confidence: 99%
See 1 more Smart Citation
“…This hybrid photonic integration coupling induced by TPP paves the way for automated assembly of photonic multi-chip systems with unprecedented performance and versatility. For multi-fiber integrated microoptics, this group also demonstrated a highly compact scanningprobe microscopes (SPM) with integrated optical actuation and read-out (Dietrich et al, 2020), as shown in Figure 3F. The SPM engine was composed of cantilevers and probe tips, and integrates optical actuation and read-out by combining mirrors and lenses.…”
Section: Micro-opticsmentioning
confidence: 99%
“…(E) Free-form lenses, free-form mirrors and beam expanders for the coupling between the optical fiber end face and the chip interface (Dietrich et al, 2018). (F) Scanning-probe microscope (SPM) with integrated optical actuation and read-out based on fiber array (Dietrich et al, 2020).…”
Section: Optical Waveguide Devicesmentioning
confidence: 99%
“…Recently, it was shown that scanning-probe microscopy (SPM) engines consisted of cantilevers, tips, a wide variety of actuator and read-out elements can be produced employing MPL. It is expected, that MPL could enable a mass fabrication of SPM arrays, which is unavailable by current approaches [259]. Combining MPL with electrochemical deposition, thermal evaporation, or sputtering truly arbitrary 3D design magnetic nanostructures (magnetic nanowires, multi-segmented nanowires, nanotubes, etc.)…”
Section: Current Applicationsmentioning
confidence: 99%
“…Much effort has been devoted to improving the processing accuracy, and spatial resolutions as low as micrometers have been achieved in laser cutting, welding, marking, and stereolithography in an atmospheric environment [3][4][5][6] . The femtosecond laser (fs laser) is a particularly promising approach from this point of view, in addition to its three-dimensional (3D) processing capability [7][8][9][10][11][12] and broad-spectrum material usability [13][14][15][16][17][18] . Sub-diffractionlimited feature sizes at a level of tens of nanometers based on multiphoton absorption 19,20 , thresholding 21 , shrinkage 22,23 , and stimulation emission depletion effect 24,25 , have also been realized in fs-laser-induced photocuring of polymers, which unfortunately are not applicable to solid materials.…”
Section: Introductionmentioning
confidence: 99%